Evolutionary stage, anthropogenic activities and evolution of the Itapeva dunefield (Torres-RS, Brazil) - Rockett, Gabriela Camboim; Barboza, Eduardo Guimarães; Fagundes, Marina Refatti; Hesp, Patrick; Rosa, Maria Luiza Correa da Câmara (Quaternary and Environmental Geosciences, 2021)
Transgressive coastal dunefields dominate the southern coast of Brazil, and few studies are investigating the factors driving their historical changes. The aim of this study is to investigate spatio-temporal changes over the last 60 years in the Itapeva coastal transgressive dunefield (northern coast of Rio Grande do Sul state) and also the factors influencing these changes. The dunefield is analyzed via various methods including (i) spatial and temporal analyses of the dunefield utilizing aerial photography, satellite imagery and Geographic Information System, (ii) climatic analysis from 1961 to present and (iii) sand drift calculations. The results show a significant decrease in the mobile dunes area since 1953, an increase in vegetation cover, and an increase in urbanization area. While anthropogenic factors have influenced the dunefield (e.g. sediment removal and urbanization development), results of this study show that an increase in rainfall and decrease in average wind velocity are also responsible for the main spatial changes, vegetation colonization and stabilization processes in the Itapeva dunefield. The dunefield has also evolved into a new stage where deflation basin development and enlargement has encouraged vegetation colonization and expansion